The Status Quo of Corruption Eradication in Indonesia: Reinterpreting Friedman’s Legal System Theory in the Era of the New Criminal Code - Taufik Tri Prabowo; Marnija; Raden Ferdiandra Defry Yusdanial; Hans Karyose; Muhammad Anshari (CV. Norma Global, 2026)
Corruption remains one of the most persistent structural challenges in Indonesian governance. Despite a relatively dense anti-corruption legal architecture, the Indonesian anti-corruption regime has not produced consistent and transformative results. This article examined the status quo of corruption eradication in Indonesia through Lawrence M. Friedman's legal system theory, focusing on the interaction among legal substance, legal structure, and legal culture. Using normative juridical research supported by conceptual, statutory, and systems-oriented analysis, the study assessed the implications of the recodification of corruption offences in Law Number 1 of 2023 on the Criminal Code, the fragmentation of institutional mandates among the Corruption Eradication Commission, the Attorney General's Office, and the National Police, and the persistence of permissive social attitudes toward corrupt practices. The findings showed that each component of Friedman's legal system exhibits a distinct dysfunction that reinforces the others, producing a feedback loop in which formal anti-corruption instruments fail to generate substantive change. The article concluded that sustainable corruption eradication requires simultaneous harmonisation of legal norms, coordinated institutional reform, and transformation of public integrity culture.